Housing, debt and the economy: a tale of two countries - Muellbauer, J (University of Oxford, 2018)
In housing affordability levels and volatility, there could hardly be a greater contrast than between the UK and Germany. Differences in history, institutions and policies are explored in this paper. Residential housing supply has been far more expansionary in Germany and mortgage credit more tightly regulated. A sensibly regulated rental market and stable German house prices have combined to leave the rental sector with over half of tenures. Policy failures in the UK have resulted in widening intergenerational inequality, increased social exclusion, adversely affected productivity and growth and raised the risk of financial instability. Policy lessons are drawn for the UK, which go far beyond the remit of the immediately responsible Ministry of Housing, Communities and Local Government.